Fabrication of SiNWs/Graphene nanocomposite for IR sensing. (2020) - Kumar, Avshish; Mir, Qamar Ali; Kumar, Amit; Dhasmana, Hrishikesh; Husain, Samina; Kumar, Vivek; Verma, Abhishek; Jain, V.K.
Abstract: Silicon Nanowires (SiNWs) on 10Ώ p-Si(1 0 0) were synthesized in HF/AgNO3 solution via single setup metal assisted chemical etching method. Then SiNWs were decorated using Graphene for IR sensing. The fabrication of SiNWs/Graphene was confirmed by scanning electron microscope (SEM), and transmission electron microscope (TEM). The NIR photo-resistive response of SiNWs/Graphene was measured using near infra-red (1064 nm) illumination at Room temperature. From the photo-resistive response of SiNWs/Graphene, the initial resistance (before IR exposure) of 11.8 kΩ was observed which was abruptly decreased to 10.2 kΩ under IR illumination. After turning off IR source lamp, the resistance recovered very promptly to its initial base value. The sample was checked repeatedly for four cycles of on-off illumination period of 5 s. Therefore, from the results, it can be concluded that SiNWs/Graphene IR sensor has shown the good responsivity and fast recovery to its initial base region.